After Woolwich: Analyzing Open Source Communications to Understand the Interactive and Multi-polar Dynamics of the Arc of Conflict. (7th April 2017) - Roberts, Colin; Innes, Martin; Preece, Alun; Rogers, David
Abstract: This article is based upon a case study of the 2013 murder of Fusilier Lee Rigby in Woolwich, London. It shows how analysis of open source communications data collected via social media platforms can illuminate the inter- and intra-community conflict dynamics arising in the aftermath of such events. Framed by Collins' recent theoretical work on the escalatory and de-escalatory forces in conflict situations, the empirical analysis brings to the fore some new insights about the 'arc of conflict'. These frame a conceptual accent upon the interactive sequences of mobilization and counter-mobilization occurring in the moves towards group-based conflicts, and the importance of understanding the multi-polar nature of these involvements.